(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2013)
Prenatal care is an essential segment of maternal health-care. In this paper an attempt has been made to examine the socioeconomic determinants of maternal iron supplementation and sufficient maternal iron supplementation as components of prenatal care. Micro-data having 25999 and 19764 observations for two models, i.e. maternal iron supplementation and maternal sufficient iron supplementation respectively has been taken from Indian Demographic and Health Survey (IDHS) 2005-6. To estimate the probability in both the models binary logistic regressions have been employed. The explanatory variables categorized into individual characteristics of the woman, household characteristics, health-related characteristics, community characteristics and regional characteristics have been embraced in the analysis. The results of the first model revealed that probability of iron supplementation is augmented by woman’ education, woman’ age at first marriage, woman’s working status, husband’s age, husband’s education, husband’s presence at prenatal visit, final say on woman’s health (by woman, woman and husband collectively and even husband alone as compared to someone else) and household covered by the health insurance. The birth-order of the child, woman’s living in small city and town as well as wealth index of the household slides down the probability of iron supplementation. The estimates of the second model explained that probability of sufficient iron supplementation is positively influenced by woman’s age at first marriage, woman’s education, husband’s age, husband’s presence at prenatal visit, final say on woman’s health-care (husband alone) and household wealth. The birth-order of the child and small city as place of residence negatively affect the likelihood of sufficient iron supplementation. The study proposed the targeted approach to enhance iron supplementation and sufficient iron supplementation in Indian women. The marginalized households should be targeted through cash transfer programs. Furthermore, the small cities and country sides should also be focused. The awareness and education of woman along with husband’s participation in maternal health care cannot be ignored in policy making.